To teach or not to teach? The question of the academic librarian's pedagogical competencies in the digital age - Raju, J. (South African Journal of Higher Education, 2017)
This paper revisits the issue of ‘librarian as teacher’ in the literature and draws empirical evidence on the question of the pedagogical knowledge and skills requirements of academic librarians. A pragmativist paradigm and both quantitative and qualitative philosophical assumptions are used to address this research problem. The paper reports on the outcome of content analysis of academic library job advertisements for professional library and information services positions in South Africa, supported by findings from websites of South African LIS schools and selected data from a 2015 national online survey of academic librarians in South Africa. Such an analysis, framed by Shank and Bell’s (2011, 105) concept of “disruptive innovations” leading to their framework for blended librarianship, is used to ascertain the pedagogical competency requirements of the academic librarian in South Africa in the current digital age. The findings include a list of pedagogical competency requirements for academic librarians and provide a critical narrative, in the context of international trends and the study’s conceptual framing, on the extent to which academic librarians in South Africa meet these requirements.